Initial evaluation of the modified step-wise regression procedure to estimate aircraft stability and control parameters from flight test data - Hoff, J. C. (Cranfield University, 1993)
This report presents the initial results of research in progress in the College of Aeronautics at the Cranfield Institute of Technology. The object of the research is to investigate the use of the Modified Stepwise Regression procedure to estimate aircraft stability and control parameters from flight test data. The Stepwise Regression Method for parameter identification is a procedure that inserts independent variables into a regression model. Each time a new variable is added to the model a regression is performed and the fit is examined when the new variable, or any other previously included variable, may be rejected from the model if non-significant to the fit. The iterative process continues until a satisfactory fit (or model) is obtained.